2009
DOI: 10.1186/1472-6793-9-16
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of excitation-contraction coupling in mouse cardiac myocytes: integrative analysis with mathematical modelling

Abstract: BackgroundThe cardiomyocyte is a prime example of inherently complex biological system with inter- and cross-connected feedback loops in signalling, forming the basic properties of intracellular homeostasis. Functional properties of cells and tissues have been studied e.g. with powerful tools of genetic engineering, combined with extensive experimentation. While this approach provides accurate information about the physiology at the endpoint, complementary methods, such as mathematical modelling, can provide m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 87 publications
0
25
0
Order By: Relevance
“…) and CaMKII (Koivumaki et al . ; Edwards et al . ) regulation of mouse excitation–contraction coupling (ECC).…”
Section: Introductionmentioning
confidence: 99%
“…) and CaMKII (Koivumaki et al . ; Edwards et al . ) regulation of mouse excitation–contraction coupling (ECC).…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, an everincreasing number of detailed biophysical models of the ionic currents in ventricular myocytes underlying action potential (AP) generation have been developed (Fink et al 2011;Winslow et al 2011). Species-specific models have been published for a number of species including guinea pig Rudy 1991, 1994), rat (Pandit et al 2001), mouse (Bondarenko et al 2004;Wang and Sobie 2008;Koivum€ aki et al 2009;Li et al 2010), and human (ten Tusscher et al 2004;Bueno-Orovio et al 2008) as it was found to be necessary to account for species-specific differences in current contributions to the AP. More recently, important developmental changes in cardiac electrophysiology of mouse myocytes have been identified (Nuss and Marban 1994;Wang et al 1996;Wetzel and Klitzner 1996;Wang and Duff 1997;Sabir et al 2008;Wang and Sobie 2008;Korhonen et al 2009;Kawamura et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To date, one of the most influential mouse cardiomyocyte models was developed by Bondarenko and colleagues in 2004 [5]. Their model has been adapted by numerous groups to study the molecular regulation of ECC, myosin cross-bridge cycling and contraction, as well as whole-heart function [611]. While these modeling efforts have provided exciting new data, they contain two critical features, common in many cardiac Ca 2+ signaling models, that limit their mechanistic relevance: 1) They use a single “local [Ca 2+ ] i ” level that is identical for all RyR2s and LCCs (i.e., common pool) [5,1222].…”
Section: Introductionmentioning
confidence: 99%